First Dutch Consensus of Pain Quality Indicators for Pain Treatment Facilities. Issue 1 (22nd July 2015) - de Meij, Nelleke; van Grotel, Marloes; Patijn, Jacob; van der Weijden, Trudy; van Kleef, Maarten
Abstract: Background: There is a general consensus about the need to define and improve the quality of pain treatment facilities. Although guidelines and recommendations to improve the quality of pain practice management have been launched, provision of appropriate pain treatment is inconsistent and the quality of facilities varies widely. The aim of the study was to develop an expert‐agreed list of quality indicators applicable to pain treatment facilities. The list was also intended to be used as the basis for a set of criteria for registered status of pain treatment facilities. Methods: The University Pain Center Maastricht at the Department of Anesthesiology and Pain Management of the Maastricht University Medical Center conducted a 3‐round Delphi study in collaboration with the Board of the Pain Section of the Dutch Society of Anesthesiologists (NVA). Results: Twenty‐five quality indicators were selected as relevant to 2 types of pain treatment facilities, pain clinics and pain centers. The final expert‐agreed list consisted of 22 quality indicators covering 7 quality domains: supervision, availability of care, staffing level and patient load, quality policy, multidisciplinarity, regionalization, and research and education. Conclusions: This set of quality indicators may facilitate organizational evaluation and improve insight into service quality from the perspectives of patients, pain specialists, and other healthcare professionals. Recommendations for improvements to the current set of quality indicators are made. In 2014 the process of registering pain treatment facilities in the Netherlands started; facilities can register as a pain clinic or pain center.